Pengembangan Bahan Pembelajaran IPA Berbasis Biotechnopreneurship untuk Melatih Life Skills Siswa SMP - Nurhaningtyas Agustin; Muslimin Ibrahim; Wahono Widodo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2016)
This study aims to produce biotechnopreneurship-based science learning materials that are valid, practical, and effectiveto facilitate junior high school students’ life skills. This research is development research using a 4D development model that produces Biotechnopreneurship-based science learning materials equipped with the syllabus, lesson plan, student worksheets, life skills tests. Learning materials were tested on 35 junior high school students with the one-group pretest-posttest design. Data analysis is descriptive qualitative with the results: (a) validation of learning materials with valid categories (score 3-4); (b) readability of learning materials with good categories (c) implementation of learning in good categories (score 3.7); (d) student responses were positive; (e) students’life skills generally increase (N-gain 0.71 with high category). The indicator of Life Skills that experiences the most significant increase between pre test and post test is the aspect of making a decision. Indicators of information gathering are indicators that have a low increase after learning. Based on the results of the study it can be concluded that the biotechnopreneurship-based science learning materials are valid, practical, and effective to facilitate junior high school students’ life skills.